The archaeology of Skye and the Western Isles - Armit, Ian (Archaeologist) (Edinburgh University Press in association with Historic Scotland, 1996)
From the Callanish stones and the great ritual monuments of the Neolithic, the broch towers and the wheelhouses of the Iron Age, through to the arrival of the Norse and the Lords of the Isles, this book explores the history of human settlement and society from the first hunter-gatherers to the Clearances. What emerges is a Hebridean archaeology as distinctive as those of Orkney and Wessex.